O Brãgavata Purãna: sua doutrina e contribuições para a teoria educacional - Moura, Gustavo Henrique Passos (2017)
This Master's dissertation initially presents an exegetical and introductory study of the Bhãgavata Purãna to then explore the text’s worldview in pursuit of a model of reality and a pedagogical method that may contribute to current debates on the goal and practice of Education. By establishing a dialogue between the concepts of the Bhãgavata Purãna and the work "Education and Spirituality" of Professor Ferdinand Röhr, it is envisioned here an educational proposal oriented by values rooted in a transcendent dimension, but which contemplates the integral development of the human being in all its other dimensions as well. Among different topics addressed in this work are a correlation between the purpose of human life and the educational goal, the need for a multidimensional approach to the human being, the importance of some sort of pedagogical ethics that acknowledges and values innate differences between people, and a paradox involving educational theories of correspondence and autonomy. Complementing the theoretical approach of the two initial chapters, the dissertation ends by discussing the results of a field research conducted at the Jaladuta Institute, an educational institution affiliated to ISKCON (International Society for Krishna Consciousness) whose pedagogical model centers on spirituality.